MENELISIK NERACA PERDAGANGAN INDONESIA DARI FAKTOR INFLASI DAN KURS - Muh Agung Permana; Herman Sjahruddin; Reni Satriani; Indrawati Indrawati; Muhammad Arfandi A. Caronge; Arwinni Ratu M (LP2M Universitas Bina Bangsa, 2023)
This study aims to determine the effect of inflation, exchange rates on the trade balance in Indonesia. This research uses quantitative methods and analysis used by panel data analysts. Data collection in this study was sourced from the Central Statistics Agency (BPS). The testing of this study used Eviews 12 with a sample number of 27 provinces with a total of 108 units. The results of the first panel data analysis prove that the inflation variable has a negative and insignificant effect on the trade balance, while the exchange rate has a negative and significant influence on the trade balance in Indonesia. The result explains that lower inflation will result in an increase in the trade balance. Meanwhile, the higher the exchange rate will result in a low trade balance